2006
DOI: 10.1093/her/cyl102
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school smoking policies and student perceptions of enforcement on school smoking prevalence and location of smoking

Abstract: The purpose of this study was to comprehensively assess the impact of school tobacco policy intention, implementation and students' perceptions of policy enforcement on smoking rates and location of tobacco use during the school day. Data were obtained from all students in Grades 10-11 (n = 22,318) in 81 randomly selected schools from five Canadian provinces. Policy intention was assessed by coding written school tobacco policies. School administrators most familiar with the tobacco policy completed a survey t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 17 publications
8
70
0
3
Order By: Relevance
“…The findings from this study build on previous research 6,14,29 in that the wider school and community context is associated with adolescent smoking. In a national sample of schools followed over 3 years, we found that schools were more likely to have low smoking rates if they had a strong focus on prevention programming and when cigarette prices near the school were higher.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The findings from this study build on previous research 6,14,29 in that the wider school and community context is associated with adolescent smoking. In a national sample of schools followed over 3 years, we found that schools were more likely to have low smoking rates if they had a strong focus on prevention programming and when cigarette prices near the school were higher.…”
Section: Discussionsupporting
confidence: 78%
“…Previous findings from this study have suggested that significant differences exist in tobacco retailer variables between schools with high and low smoking rates, 6,25 that smoking rates vary across schools, and that policy characteristics can explain some of this variation. 6,14,29 Evidence has also shown that community characteristics are related to smoking rates. 6 However, evidence is lacking regarding how multiple factors, across school and community environments, work in combination and over time…”
Section: And Inmentioning
confidence: 99%
“…Students' perceptions are an indicator of policy implementation and provide a different type of information than what is stated in an official policy document. Two studies examining the Canadian context and using similar methodology as the present study found that student perceptions of policy enforcement predicted school smoking prevalence (R 2 = 0.36) [10] when the policy itself did not and students' perceptions of policy enforcement predicted nonsmoking in elementary (OR = 0.39) but not secondary schools [19].…”
Section: Introductionmentioning
confidence: 71%
“…Since adolescents spend a large proportion of their waking hours at school, they are an ideal setting in which to implement tobacco control strategies. Schools in many developed countries, such as Canada, the United States, the United Kingdom, New Zealand, and Australia, have adopted written smoking policies that prohibit tobacco use [7][8][9][10][11]. Such policies are meant to restrict exposure to second-hand smoke, support changes in social norms about smoking, and create a supportive environment for prevention and cessation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation